Hepatic artery pseudoaneurysm: three case reports and literature review - Zhao, Yuan-Quan; Yang, Yong-Yu; Yao, Si-Yang; Dong, Xiao-Feng (Frontiers in Medicine, 2024)
Laparoscopic surgery is extensively applied in the treatment of hepatobiliary diseases. Hepatic artery pseudoaneurysm (HAP) is a rare complication following hepatic biliary surgery through laparoscopy. The clinical manifestations of HAP are diverse and can be fatal. Given its severity, rapid assessment and management are crucial to ensuring a good prognosis. Here, we report three cases of HAP; two underwent laparoscopic surgery due to cholelithiasis, and another caused by trauma.The first case exhibited a pseudoaneurysm involving the distal portion of the right hepatic artery main trunk. The second patient had a pseudoaneurysm at the bifurcation of the left and right hepatic arteries. The third case involved a patient with a pseudoaneurysm involving a branch of the right hepatic artery. The main clinical manifestations of all three cases were bleeding from the biliary tract (the first two cases showed postoperative bleeding in the T-tube, while the third case exhibited gastrointestinal bleeding). The final diagnosis was obtained through digital subtraction angiography. The three patients underwent successful transcatheter arterial embolization operation and a follow-up revealed they were disease-free and alive. This article aims to highlight a rare complication of laparoscopic hepatobiliary surgery and share our experience in early diagnosis and treatment of HAP.